Whitening Efficacy of Toothpastes on Coffee-Stained Teeth: An Enamel Surface Analysis - Soyeon Kim; Chang-Ha Lee; Sunyoung Ma; Young-Seok Park (International Dental Journal, 2024)
Aim: This study aimed to identify the optimal toothpaste for removing coffee-induced stains while also evaluating its impact on tooth enamel through roughness and abraded depth parameters, providing a comprehensive understanding of their effects. Materials and methods: Three whitening toothpastes and 2 conventional toothpastes were prepared for a simulated brushing procedure on coffee-stained bovine enamel tooth specimens. Using a toothbrushing machine, up to 10,000 brushstrokes were completed, while spectrophotometric readings were taken at designated intervals. A mixed-effects model for statistical analysis determined the effects of toothpaste and brushing on colour change, roughness, and abraded depth. Results: Whitening toothpastes significantly deviated from the control (P < .001, P < .001, and P < .003, respectively), whereas the conventional toothpaste did not exhibit a significant contrast (P < .081). Regarding colour restoration following coffee staining, whitening toothpastes showed higher restoration than conventional toothpastes. Surface roughness and abraded depth parameters increased with accumulated brushing. Conclusions: Sodium hexametaphosphate-containing toothpaste demonstrated the highest efficacy in removing coffee-induced stains and restoring tooth colour. Nevertheless, this stronger whitening effect was associated with increased abrasion. While conventional toothpastes exhibited some whitening effects, the most substantial improvement in lightness was consistently observed with whitening toothpastes. Clinical Relevance: Understanding how whitening toothpaste affects enamel integrity is crucial for refining formulations and advancing dental care. This knowledge lays the groundwork for more effective oral care products and improved whitening procedures, ultimately enhancing the overall quality of dental treatments.